Measurement, reporting, and verification of methane emissions from natural gas and LNG trade: Creating transparent and credible frameworks - Jonathan P. Stern (The Oxford Institute for Energy Studies, 2022)
The Global Methane Pledge to reduce emissions by at least 30 per cent by 2030, was signed by more than 100 countries at the COP26 Conference in November 2021. Reducing methane emissions from fossil fuel sources by up to 75 per cent by 2030 has been identified as an essential contribution to reducing the rate of global temperature increase. The EU Methane Strategy proposed the establishment of a methane intensity standard for domestically produced and imported fossil fuels, with an initial focus on emissions from natural gas and LNG imports, however no such standard is included in the 2021 legislative proposals. Of the six major pipeline gas and LNG suppliers to Europe, Norway has progressed MRV and reduced emissions to a much greater extent than other major exporters to Europe. The complexity of the US LNG export supply chain, with huge numbers of production locations and multiple pipelines and processing plants contrasts with the relative simplicity of the Qatari supply chain. In the case of Russia, the focus is on Gazprom's long transmission pipelines, while Algerian and Nigerian companies are only just beginning to address these issues. European buyers will need to establish supply chain emission values with exporting companies, and possibly also with governments. Asian importers will need to agree similar values with their LNG suppliers. The SGE and GIIGNL methodologies, published in late 2021, combined with the study of Cheniere's 2018 cargos and its commitment to provide individual cargo emission tags from 2022, are important milestones in the creation of frameworks for establishing LNG supply chain emission values. By contrast, `carbon-neutral' LNG cargos lack MRV ransparency and therefore environmental credibility. Transparent MRV of emissions has become a non-negotiable requirement for the international gas community. A lack of this information undermines claims that natural gas can play a significant ongoing role in the low carbon energy transition. The longer it takes to establish such documentation, the more likely it is that countries will adopt alternative energy options.
Keywords: 330; carbon-neutral; Emissions; flaring; fugitive; GWP; IMEO; LNG; measurement; Methane; Natural gas; Reporting; venting; verification